Community-Based Education and Health Screening for Chronic Disease Complications (Stroke and Heart Disease) - Janwar olang; Bima Adi Saputra; Erniyati Fangidae; Ballsy C. A. Pangkey; Veronica Paula (English Lecturers and Teachers Association (ELTA), 2026)
Chronic diseases such as stroke and heart disease remain leading causes of morbidity and mortality in Indonesia, particularly among middle-aged and elderly populations. Limited awareness and inadequate routine health screening contribute to delayed detection and complications. This community service program aimed to enhance public knowledge about chronic disease complications and to facilitate early identification of risk factors in Oebobo District, Kupang City. The activity, conducted on March 22, 2025, involved 36 participants aged 30-74 years and included health education sessions, interactive discussions, and basic examinations consisting of blood pressure, blood glucose, cholesterol, and uric acid assessments. A pre test – post test design was used to measure knowledge improvement, while a structured questionnaire assessed participant satisfaction. The results showed a significant increase in knowledge, with mean scores improving from 47.22 to 89.58. Several participants were found to have abnormal clinical indicators requiring further medical evaluation, underscoring the need for accessible community-level screening. Overall satisfaction was very high, with a total score of 37.83 out of 40 (94.57%), reflecting strong acceptance of the activity. Although attendance was affected by unfavorable weather, participants demonstrated high enthusiasm and engagement. In conclusion, this initiative effectively improved community knowledge and supported early detection of chronic disease risk factors. Regular and sustainable implementation is recommended to strengthen preventive health efforts in the population. Keywords : Chronic disease complications; stroke; heart disease; health screening